Hybrid Procedure (Endo/Epicardial) versus Standard Manual Ablation in Patients Undergoing Ablation of Longstanding Persistent Atrial Fibrillation: Results from a Single Center. (25th February 2016) - EDGERTON, ZACHARY; PERINI, ALESSANDRO PAOLETTI; HORTON, RODNEY; TRIVEDI, CHINTAN; SANTANGELI, PASQUALE; BAI, RONG; GIANNI, CAROLA; MOHANTY, SANGHAMITRA; BURKHARDT, J. DAVID; GALLINGHOUSE, G. JOSEPH; SANCHEZ, JAVIER E.; BAILEY, SHANE; et al.
Hybrid versus Endocardial Ablation for LSPAF: Introduction: Ablation of longstanding persistent atrial fibrillation (LSPAF) is the most challenging procedure in the treatment of AF, either by surgical or by percutaneous approach. Objective: We investigated the difference in success and complication rates between combined surgical epicardial and endocardial catheter ablation procedure and our standard endocardial ablation procedure. Methods and Results: Twenty‐four consecutive patients (group 1) with LSPAF and enlarged left atrium (>4.5 cm) underwent a combined procedure, consisting of surgical, closed‐chest, epicardial, radiofrequency ablation (nContact, NC, USA) via pericardial access, and concomitant endocardial ablation (hybrid procedure). Procedural complications and long‐term outcomes were compared to those of 35 consecutive patients who refused the hybrid procedure and underwent standard endocardial only ablation (group 2). Baseline characteristics were comparable. In group 1, 1 patient (4.2%) developed post‐procedural cardio‐embolic stroke and 3 (12.5%) died (1 atrio‐esophageal fistula, 1 fatal stroke, 1 of unknown cause in early follow‐up), while no strokes or deaths occurred in group 2. Overall complication rates were higher for group 1 (P = 0.036). At 24‐month follow‐up, 4 (19%) patients in group 1 and 19 (54.3%) in group 2 were arrhythmia‐free after a single procedure, on or off antiarrhythmic drugs (P<0.001). Total procedural time (276.9 ± 63.5 vs. 203.15 ± 67.3 minutes) and length of hospital stay (5 [IQR 3–8] vs. 1 [IQR 1–3] days were significantly shorter for group 2 (P <0.001). Conclusions: In patients with LSPAF and enlarged left atrium, a concomitant combined surgical/endocardial ablation approach increases complication rate and does not improve outcomes when compared to extensive endocardial ablation only.